Acta Medica Indonesiana - The Indonesian Journal of Internal Medicine 253 Extended Dual Antiplatelet for Diabetic Elderly Patients After Drug-eluting Stent Implantation: an Evidence-based Clinical Review - Benedicta M Suwita; Purwita W Laksmi; Ika P Wijaya (Acta Medica Indonesiana)
Antiplatelet is an important drug for patients with coronary heart disease undergoing drug-eluting stent implantation. Current guidelines recommend dual antiplatelet with aspirin and a P2Y12 inhibitor for at least 12 months. Continuation of DAPT beyond 12 months may be considered for preventing very late stent thrombosis. Several patient-related factors that contribute to stent thrombosis have been recognized, including diabetes and advanced age, but the optimal DAPT duration for these patients is still controversial. This article reviews the efficacy of extended (>12 months) compared to standard (12 months) DAPT for reducing myocardial infarction and stent thrombosis rates, especially in diabetic elderly patients. Literature screening was conducted at PubMed and Cochrane database using “dual antiplatelet”, “duration”, “adult-onset diabetes mellitus”, “elderly” and, “drug-eluting stent” as keywords. Article types were limited to meta-analysis, systematic review, randomized clinical trial, or clinical trial that compared the efficacy of extended to standard duration of  DAPT. Clinical outcomes used were myocardial infarction and stent thrombosis. The initial search was done to find relevant studies specifically assessing diabetic and elderly patients, then widened to diabetic and non-diabetic patients of any age above eighteen years. A total of 5 clinical trials and 1 meta-analysis were reviewed, showing an overall risk reduction of stent thrombosis and myocardial infarction. This review has several limitations, such as its potential selection bias and underrepresented proportion of diabetic and elderly patients. High-risk subgroups like diabetes mellitus has a tendency of increased ischemic risk, while advanced age could have both increased ischemic risk and bleeding risk. This review suggests that it is better to reserve extended dual antiplatelet therapy for patients with high ischemic risk and low bleeding risk (tailored therapy). Key words: adult-onset diabetes mellitus, drug-eluting stent, extended dual antiplatelet, elderly, myocardial infarction, stent thrombosis.